The role of heuristics in sentence processing in Turkish - Dokudan, Noyan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
One of the main research areas in psycholinguistic focuses on how people understand sentences. In sentence comprehension studies, it has been shown that language users sometimes engage in ‘shallow’ processing (Barton & Sanford, 1993; Ferreira, 2003), that non-canonical sentences are often misinterpreted (Ferreira, 2003), that misinterpretations during online comprehension are due to incomplete reanalysis (Christianson et al., 2001). These findings have given way to the Good-Enough processing approach (Ferreira, 2003; Ferreira, Bailey & Ferraro, 2002; Ferreira & Patson, 2007; Sanford & Sturt, 2002; Swets, Desmet, Clifton & Ferreira, 2008; Townsend & Bever, 2001). In this approach, it is assumed that the sentence comprehension system can develop parsing strategies that are called “heuristics” and make us of these “shortcuts” (Swets et al., 2008). At the center of the present study lies the role of heuristics based on animacy in processing sentences. To test this, Turkish sentences including a local ambiguity are used in this study. Results of a self-paced reading experiment show that people may treat the same ambiguous sequence differently based on the animacy of the noun phrases that make up the sequence. In addition, the disambiguation of the locally ambiguous sequence may also be affected by the animacy of the noun phrases in the sequence.
Keywords: Psycholinguistics.; Grammar, Comparative and general -- Sentences.